Infidelity proneness: the role of parenting styles and attachment styles - سولماز جوادی; علی زینالی (فصلنامه خانواده پژوهی, 2019)
This study intends to examine whether the different styles of parenting through the creation of different attachment styles can be effective in marital infidelity proneness. Participants in the study who were 268 married students ranging from 20 to 46 years old were selected by cluster random sampling method based on gender and educational groups. Data were collected by parenting styles questionnaire, attachment styles questionnaire, and infidelity proneness questionnaire. The data were analyzed using correlation and path analysis. The results show that authoritative parenting style by creating a secure attachment has no role in infidelity proneness. Authoritarian, permissive, and neglectful parenting styles through the creation of insecure attachment has effects in infidelity proneness . This study emphasizes the fundamental role of parenting styles and attachment styles in the handling of marital bright future and recommends the parents learning authoritative parenting style and changing the authoritative, permissive, and neglectful parenting styles.